Feasibility Study of Mernek Milik Kita Program (MERLITA) using Social Return on Investment (SROI) Method - Retno Suryani; Nurani Ikhlas (Universitas Diponegoro, 2021)
The MERLITA (Mernek Milik Kita) program is a community development program for PT Pertamina (Persero) Fuel Terminal Maos Cilacap, which was carried out in Mernek Village, Maos District, Cilacap Regency. This program aims to increase the income of farmers and farm laborers by changing the function of planting rice for consumption into superior seeds. In addition, it also encourages environmentally friendly and sustainable agricultural practices because these seeds can reduce the use of urea which can reduce greenhouse gas emissions. The MERLITA program has a significant impact on economic and environmental development in Mernek Village, the community around Mernek village feels the impact. Therefore, in this paper, the results of the Impact Assessment of the program using the SROI method will be given. The measurement results obtained the value of the SROI ratio of 1.34, indicating that every 1 rupiah invested has an impact value of Rp. 1.34. This situation proves that the MERLITA Program is still feasible to be conducted and still positively impacting Mernek Village economy.